2019
DOI: 10.1088/0256-307x/36/2/028102
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Two-Dimensional AgTe Monolayer Atomic Crystal on Ag(111) Substrate

Abstract: We report on the formation of two-dimensional monolayer AgTe crystal on Ag(111) substrates. The samples are prepared in ultrahigh vacuum by deposition of Te on Ag(111) followed by annealing. Using a scanning tunneling microscope (STM) and low electron energy diffraction (LEED), we investigate the atomic structure of the samples. The STM images and the LEED pattern show that monolayer AgTe crystal is formed on Ag(111). Four kinds of atomic structures of AgTe and Ag(111) are observed: (i) flat honeycomb structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…As in the case of CuSe, the various distortions of the honeycomb layer were clearly revealed by additional diffraction spots in the LEED patterns. In ref , STM data from a AgTe sample annealed at 500 K showed a striped structure resembling that of the striped structure discussed in ref . The large size of the AgTe spots in the LEED pattern in ref is consistent with the presence of several unresolved spots, as expected from a distorted honeycomb layer.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…As in the case of CuSe, the various distortions of the honeycomb layer were clearly revealed by additional diffraction spots in the LEED patterns. In ref , STM data from a AgTe sample annealed at 500 K showed a striped structure resembling that of the striped structure discussed in ref . The large size of the AgTe spots in the LEED pattern in ref is consistent with the presence of several unresolved spots, as expected from a distorted honeycomb layer.…”
supporting
confidence: 63%
“…This deviation from an ideal honeycomb structure resulted in a splitting of the CuSe spots in the low-energy electron diffraction (LEED) pattern from the CuSe layer . A honeycomb structure has also been reported for 2D layers of AgTe on Ag(111) in two recent studies. , STM and LEED results from a sample annealed at 720 K, in ref , showed different structures denoted as buckled, with ridges and trenches, and striped with uniaxially elongated honeycombs. As in the case of CuSe, the various distortions of the honeycomb layer were clearly revealed by additional diffraction spots in the LEED patterns.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…The adsorption sites of Te adatoms were determined with the surrounding reference CO molecules adsorbed at the top sites of Ag(111) surface, as shown in Fig. 2 After the deposition of Te atoms on the Ag(111) surface, the following annealing process was performed to form the AgTe monolayer film [36][37] . A large-scale STM image of the formed AgTe monolayer is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Another way that strain is relieved is the emergence of an array of holes in the mixed area, which is similar to other systems studied previously. In reports on CuSe grown on a Cu(111) substrate 38 and AgTe grown on a Ag(111) substrate, 39 it was shown that the removal of atoms gives rise to maximum gain in energy and leads to the formation of an ordered array of vacancies. In our system, such holes are also formed, as highlighted by the orange triangle and the orange trapezoid in Figure 3d.…”
mentioning
confidence: 99%